2020
DOI: 10.1101/2020.09.09.290502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-read sequencing reveals rapid evolution of immunity- and cancer-related genes in bats

Abstract: Bats are exceptional among mammals for harbouring diverse pathogens and for their robust immune systems. In addition, bats are unusually long-lived and show low rates of cancer. Contiguous and complete reference genomes are needed to determine the genetic basis of these adaptations and establish bats as models for research into mammalian health. Here we sequenced and analysed the genomes of the Jamaican fruit bat (Artibeus jamaicensis) and the Mesoamerican mustached bat (Pteronotus mesoamericanus). We sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 237 publications
1
8
0
Order By: Relevance
“…This indicates a substantially higher gene completeness in our assemblies, similar to the most contiguous bat assemblies generated to date ( Fig. 1C ) ( 25 , 26 ).…”
Section: Resultssupporting
confidence: 59%
“…This indicates a substantially higher gene completeness in our assemblies, similar to the most contiguous bat assemblies generated to date ( Fig. 1C ) ( 25 , 26 ).…”
Section: Resultssupporting
confidence: 59%
“…Consistent with a previous HiFi-based bat assembly 40 , we estimate a very high base accuracy (QV=61.8-69.7, indicating <1 error per megabase) for our nine HiFi-based assemblies. These base accuracy values are two orders of magnitude higher compared with previous PacBio CLR or Nanopore-based assemblies 28,29 .…”
Section: Ten New Reference-quality Chromosome-level Genomes Of Batsmentioning
confidence: 67%
“…For Chiroptera, we included the 10 new and ten previously published bat assemblies. 18 of these 20 bats were assembled from long sequencing reads 28,29,40 while the remaining two genomes were assembled from Illumina short-read data 149,150 (Supplementary Table 3). For five mammalian orders (Primates, Rodentia, Cetartiodactyla, Carnivora, Chiroptera), we selected exactly 20 species.…”
Section: Selection Of Non-chiropteran Genome Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this unique distribution and expression of IRF7 was not detected in other bat species, such as Rousettus aegyptiacus (Pavlovich et al, 2018), although similar results have been observed in some species of fish, such as the crucian carp (Carassius auratus L.) (Zhang et al, 2003). Thus, different bat species may have evolved alternative antiviral strategies, including a potential shift toward an IFNu driven response relative to IFNa in at least 10 bat species (Scheben et al, 2021). Additionally, positive selection of a serine residue at the 185 th position in IRF3 has been shown to have enhanced antiviral properties in E. fuscus and P. alecto bat cells (Banerjee et al, 2020d).…”
Section: Innate Immune Responsementioning
confidence: 99%